2014
DOI: 10.1371/journal.pone.0097364
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Genome-Wide Chromosomal Histone Modification Patterns in Maize Cultivars and Their Wild Relatives

Abstract: Recent advances demonstrate that epigenome changes can also cause phenotypic diversity and can be heritable across generations, indicating that they may play an important role in evolutionary processes. In this study, we analyzed the chromosomal distribution of several histone modifications in five elite maize cultivars (B73, Mo17, Chang7-2, Zheng58, ZD958) and their two wild relatives (Zea mays L. ssp. parviglumis and Zea nicaraguensis) using a three-dimensional (3D) epigenome karyotyping approach by combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
2
13
1
Order By: Relevance
“…Although in prior work we did not find a clear H3K9me2 knob staining pattern in meiotic chromosome spreads or interphase mitotic root cells (Shi and Dawe, 2006), more recent cytogenetic data from root tip chromosomes (He et al, 2014) and ChIP-seq data from developing ear tissue reported herein clearly show that knobs are marked by H3K9me2 ( Figure 3C). Neither type of knob repeat showed any evidence of RdDM as assayed by 24-nucleotide siRNAs (Supplemental Figure 4A).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Although in prior work we did not find a clear H3K9me2 knob staining pattern in meiotic chromosome spreads or interphase mitotic root cells (Shi and Dawe, 2006), more recent cytogenetic data from root tip chromosomes (He et al, 2014) and ChIP-seq data from developing ear tissue reported herein clearly show that knobs are marked by H3K9me2 ( Figure 3C). Neither type of knob repeat showed any evidence of RdDM as assayed by 24-nucleotide siRNAs (Supplemental Figure 4A).…”
Section: Discussioncontrasting
confidence: 68%
“…At a molecular level, the most thorough descriptions of maize heterochromatin have been related to DNA methylation and siRNAs (Eichten et al, 2011;Gent et al, 2013;Regulski et al, 2013). Multiple other studies have provided valuable insights into the distribution of DNA methylation, nucleosomes, and histone modifications (Eichten et al, 2012;Fincher et al, 2013;Labonne et al, 2013;Makarevitch et al, 2013;He et al, 2014;Madzima et al, 2014). These studies have been limited in their application to heterochromatin, however, because of poor resolution over repetitive regions, shortage of experimental data, or a focus on genic chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between late terminal condensation region and H3K4me2 was also reported for Costus spiralis and Eleutherine bulbosa (Feitoza and Guerra 2011) as well as for inbred lines and hybrids of maize (Shi and Dawe 2006;He et al 2014). In Dimethylation in histone H3 lysine 9 is a characteristic heterochromatin mark (Feng and Jacobsen 2011), which is important for transposon silencing and for DNA methylation control (Bernatavichute et al 2008).…”
Section: Discussionsupporting
confidence: 59%
“…In wild-type Arabidopsis, CO suppression around the centromere closely reflects the increase in DNA methylation (23,38,55). In contrast, DNA methylation in maize (56) does not follow the same strongly U-shaped distribution pattern as COs (Fig. 1C).…”
Section: Mechanistic Underpinnings Of Dsb Hotspot Recognition In Maizementioning
confidence: 90%